Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858390
|View full text |Cite
|
Sign up to set email alerts
|

Smart Touch

Abstract: We present two contributions for improving the accessibility of touch screens for people with motor impairments. First, we provide an exploration of the touch behaviors of 10 people with motor impairments, e.g., we describe how touching with the back or sides of the hand, with multiple fingers, or with the knuckles creates varied multi-point touches. Second, we introduce Smart Touch, a novel template-matching technique for touch input that maps any number of arbitrary contact-areas to a user's intended (,) tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Indeed, for users with motor impairments, touchscreen tapping (i.e., pointing) errors were more than three times as high with the touchscreen than with the mouse. Tapping is by far the most common touchscreen interaction technique, which emphasizes the importance of efforts to improve tapping accuracy (e.g., [10,20]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, for users with motor impairments, touchscreen tapping (i.e., pointing) errors were more than three times as high with the touchscreen than with the mouse. Tapping is by far the most common touchscreen interaction technique, which emphasizes the importance of efforts to improve tapping accuracy (e.g., [10,20]).…”
Section: Discussionmentioning
confidence: 99%
“…While spurious touches are ignored in typical Fitts task (as in our earlier analysis), they can create problems in real systems, for example, causing an intended tap to result in a multi-finger gesture like zoom. While Mott et al [10] report on the number of touchpoints on the screen during tapping tasks, participants in that study tapped in a "comfortable and natural" way, rather than under standard conditions. To our knowledge, spurious touches have not been reported in detail for users with motor impairments.…”
Section: A Closer Look At Touchscreen Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, gesture recognition systems 2 are unlikely to work well for people with differences in morphology (e.g., a person with an amputated arm may be unable to perform bimanual gestures, or may grip a device differently than expected; a person with polydactyly's style of touching a screen may register an unanticipated pattern). Failure of gesture recognition systems is also likely in cases where disability affects the nature of motion itself, such as for someone who experiences tremor or spastic motion [56,57]. Fatigue may also impact gesture performance (and therefore recognition accuracy) over time, particularly for groups that may be more susceptible to fatigue such as due to disability or advanced age.…”
Section: Body Recognitionmentioning
confidence: 99%
“…For common touchscreen gestures like tapping, crossing and directional gesturing, Guerreiro et al [45] found that targets located at the bottom of the screen and next to the preferred hand were the easiest to select. Specific to tap gestures, while Montague et al [92] investigated touchscreen interaction behaviors in the wild and built and evaluated a novel approach to accommodate individual differences, Mott et al [94] built and evaluated a technique to accommodate multiple touch points to map the user's intended behavior. These studies highlight that mobile devices like smartphones and tablets can offer benefits like independence, but accessibility challenges still exist.…”
Section: Accessible Mobile Computingmentioning
confidence: 99%